Expression of oestrogen receptor alpha (ERα) in oral lichen planus - A precancerous inflammatory disease in middle-aged females - Abhishek Jana; Jincy Thomas; Pratiti Ghosh (Wolters Kluwer Medknow Publications, 2023)
Background: Oral lichen planus (OLP) is an autoimmune disease primarily affecting the middle-aged females. The present study aims to determine the relation of the oestrogen receptor alpha (ERα) with OLP pathogenesis, correlating it with the possible cause of its higher prevalence among females. Materials and Methods: Clinically and histologically identified fifteen of each pre-menopausal and peri-menopausal OLP female patients were chosen for this study. The expression of ERα was analysed from the collected lesion tissue samples by using two-step semi-quantitative reverse transcriptase polymerase chain reaction (SqRT-PCR) and enzyme-linked immunosorbent assay (ELISA). Results: mRNA and protein expression of ERα were significantly higher in both groups of OLP female patients when compared with the control. The perimenopausal OLP patients showed significantly elevated expression of ERα compared to premenopausal patients. Conclusion: Higher expression of ERα in pre- and peri-menopausal females may be a causative factor for the higher prevalence of OLP among females.